Development of Inquiry-Based Worksheets Assisted by PhET Simulations to Improve Students' Concept Mastery - Amri, Khairil; Herayanti, Lovy; Gummah, Syifaul (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Inquiry-based worksheets assisted by PhET simulations were developed to enhance students' concept mastery. Students' concept mastery is a variable that often becomes the focus in evaluating the effectiveness of learning aids. The purpose of this research is to develop inquiry-based worksheets assisted by PhET simulations to improve students' concept mastery. This research is a research and development (R&D) type, using the 4D development model (Define, Design, Develop, Disseminate), which in this study only involves three main stages: definition, design, and development. Data collection techniques include validation sheets, student response questionnaires, and concept mastery test instruments. The analysis results show that the worksheets are feasible with an average percentage of 75%. The student response questionnaire results show 83%, categorized as very feasible. The concept mastery test results show 80%, categorized as feasible. Thus, it can be concluded that the inquiry-based worksheets assisted by PhET simulations that were designed and developed are feasible and effective in improving students' concept mastery. This research provides an important contribution to the development of innovative and effective learning aids in the field of education.